Physiological characteristics of elite Greek female soccer players - Nikolaidis, P. T. (Medicina dello Sport, 2010)
Aim. Assessment of elite athletes' physiological characteristics is necessary in order to develop proper training, talent detection and identification programs. Since women's soccer is just at the beginning, there are no data available on elite players. Aim of this study was to investigate anthropometric and physiological characteristics of elite Greek female soccer players.